In vitro neutralization of IL-6 receptor exacerbates damage to intestinal epithelial cells during Mycobacterium avium paratuberculosis infection - Alhendi, Ala’; Naser, Saleh A. (Frontiers in Immunology, 2024)
Like TNFα, IL-6 is upregulated in Crohn’s disease (CD) especially in patients associated with Mycobacterium avium paratuberculosis (MAP) infection, and both cytokines have been targeted as a therapeutic option for the treatment of the disease despite the accepted partial response in some patients. Limited response to anti-IL-6 receptor-neutralizing antibodies therapy may be related to the homeostatic dual role of IL-6. In this study, we investigated the effects and the signaling mechanism of IL-6 involved in intestinal epithelial integrity and function during MAP infection using an in vitro model that consists of THP-1, HT-29 and Caco-2 cell lines. Clinically, we determined that plasma samples from MAP-infected CD patients have higher IL-6 levels compared to controls (P-value < 0.001). In CD-like macrophages, MAP infection has significantly upregulated the secretion of IL-6 and the shedding of (IL-6R) from THP-1 macrophages, P-value < 0.05. Intestinal cell lines (Caco-2 and HT-29) were treated with the supernatant of MAP-infected THP-1 macrophages with or without a neutralizing anti-IL-6R antibody. Treating intestinal Caco-2 cells with supernatant of MAP-infected macrophages resulted in significant upregulation of intestinal damage markers including claudin-2 and SERPINE1/PAI-1. Interestingly, blocking IL-6 signaling exacerbated that damage and further increased the levels of the damage markers. In HT-29 cells, MAP infection upregulated MUC2 expression, a protective response that was reversed when IL-6R was neutralized. More importantly, blocking IL-6 signaling during MAP infection rescued damaged Caco-2 cells from MAP-induced apoptosis. The data clearly supports a protective role of IL-6 in intestinal epithelia integrity and function especially in CD patients associated with MAP infection. The findings may explain the ineffective response to anti-IL6 based therapy and strongly support a therapeutic option that restores the physiologic level of IL-6 in patient’s plasma. A new treatment strategy based on attenuation of IL-6 expression and secretion in inflammatory diseases should be considered.